Loss of the PDLIM2 protein during chronic colitis promotes inflammation, impaired epithelium recovery, alterations to the microbiome and oxidative stress - Ward, Stephanie; Cox, Orla T.; Roggiani, Sara; Crowley, Tadgh; Turroni, Silvia; Melgar, Silvia; O’Connor, Rosemary (Frontiers in Endocrinology, 2026)
IntroductionUlcerative colitis (UC) involves impaired wound healing processes contributing to sustained immune and microbial interactions that aggravate intestinal injury and may progress to colitis-associated cancer (CAC). Here we investigated whether PDLIM2, a known regulator of both epithelial and immune cell fate, contributes to colitis progression.MethodsPDLIM2 knockout mice (-/-) and wildtype littermates (+/+) were assessed for responses to dextran sodium sulphate (DSS)-induced colitis, and to aoxymethane +DSS. Microbiota were assessed using 16s rRNA amplicon sequencing. Mechanistic studies were carried out in Caco-2 cell cultures, and in silico analysis was carried out on single cell RNA sequencing data from patients with Ulcerative colitis or Crohn’s disease.Results and discussionCompared to PDLIM2 +/+ mice, PDLIM2 -/- mice exhibited exacerbated and unresolved epithelial damage and inflammation accompanied by immune cell infiltration, which was precluded sufficient time to observe tunour development. PDLIM2 -/- mice exhibited altered basal gut microbial diversity, composition and predicted functionality compared to +/+ mice. Interestingly, in +/+ mice, PDLIM2 expression was lost over the course of DSS-induced colitis. Mechanistic studies in Caco-2 enterocyte cell cultures demonstrated that PDLIM2 suppression resulted in impaired cell adhesion signalling and sustained oxidative stress. In silico analysis of single cell RNA seq data sets from patients with ulcerative colitis and Crohn’s disease demonstrated that although PDLIM2 was clearly expressed in normal human colonic epithelial enterocyte populations, its expression declined in both ulcerative colitis and Crohn’s disease. We conclude that PDLIM2 is necessary for intestinal homeostasis through regulation of cell adhesion and antioxidant pathways, while loss of PDLIM2 sustains inflammation and epithelial damage.